Epithelial remodeling after corneal crosslinking using higher fluence and accelerated treatment time. Issue 3 (March 2018) - Haberman, Ilyse D.; Lang, Paul Z.; Broncano, Alvaro Fidalgo; Kim, Sang Woo; Hafezi, Farhad; Randleman, Bradley J.
Abstract : Purpose: : To evaluate changes in regional corneal epithelial thickness after corneal crosslinking (CXL) using higher fluence (7.2 J/cm 2 ) and accelerated treatment time (4 minutes) in eyes with progressive keratoconus using spectral‐domain optical coherence tomography (SD‐OCT) and to correlate focal epithelial and focal anterior curvature changes. Setting: : Academic medical center in the United States. Design: : Prospective case series. Methods: : Patients had anterior segment SD‐OCT (RTVue‐100) with focal stromal and epithelial measurements and Scheimpflug imaging before and 1, 3, 6, and 12 months after accelerated CXL. Results: : Twenty‐seven eyes from 20 patients were evaluated. Before the accelerated CXL, the epithelium was thinnest in the inferior inner and outer temporal regions, whereas at 12 months postoperatively, the epithelium was significantly thinned in multiple inferior and nasal regions by 1.1 to 3.2 μm ( P < .05, all measurements), with no significant changes from 6 to 12 months. Epithelial thickness standard deviation across the central 6.0 mm was significantly reduced by 3 months (1.4 μm, P = .09) and remained stable at 12 months ( P = .009). Change in epithelial thickness was poorly correlated to change in anterior curvature ( r = −0.035). Conclusions: : Significant epithelial remodeling occurred after accelerated CXL in eyes with progressive keratoconus, with improved regularity across the central 6.0 mm, by 6 months after treatment. There was poor correlation between focal epithelial thickness and anterior curvature changes, with wide variability between patients. Establishing the pattern of epithelial remodeling after CXL might help optimize future custom treatment protocols.